Nutritional management of diabetes mellitus: A single‐case study - Elida Sinuraya; Antonij Edimarta Sitanggang; Erwin Silitonga; Jastro Situmorang; Leo Rikki Saragi (Malahayati International Journal of Nursing and Health Science, 2023)
Background: An imbalance of the body's nutritional needs is a condition in which nutrient intake is insufficient to meet the metabolic needs of the body. Diabetes mellitus is a disease caused by high levels of glucose in the blood due to the body's inability to release or use insulin adequately.Purpose: to find out whether nursing interventions can meet the nutritional needs of the body in patients with diabetes mellitus.Method: This descriptive research uses a case study approach. The participant is a 68-year-old man who is 3 years old with diabetes mellitus. He felt weak, dizzy, and his legs tingled. He had no appetite and to eat, he only ate half of the plate. Their current blood sugar level is 548 mg/dl and their blood pressure is 200/94 mmHg. Intervention - within 3 days, participants were assessed on vital signs, nutritional status, and favorite foods. Participants received education about oral hygiene and important nutrition for their bodies. Participants had received insulin and a 1700-calorie diet.Results: With this intervention, participants' blood sugar levels were randomly assigned to drop from 548 mg/dl to 200 mg/dl, appetite increased, and food intake increased from half a plate to one plate. His blood pressure dropped from 200/94 mmHg to 120/80 mmHg.Conclusion: The results of these participants provide an encouraging assessment of vital signs, nutritional status, and favorite foods, education about oral hygiene and essential nutrients for the body, and collaboration of insulin diet and diabetes patients.